Public offer of shares - Matlala, David (Department of Commercial Law, 2026)
The purpose of this thesis is to look into and analyse the concept 'public offer of shares·. Our present Companies Act provides that no person shall offer any shares to the public otherwise than in accordance with the provisions of the Act. The provisions thereof prescribe that no shares shall be offered to the public unless there is an accompanying prospectus or written statement. 1. Act No. 61 of 1973 2. Section 143 3. Sections 145(1) and 146(1) 4. Section 141 In order to ensure compliance with the provisions of the Act when shares are offered to the public, there must therefore be a prospectus, which is issued, which issue should be public. The scope of this paper is thus limited to an inquiry into the prospectus itself (the meaning thereof), the 'issue' of the same and those to whom it is directed called the public. The requirements of form, content and consequences of a proper or improper prospectus fall outside the scope of this paper. The work is divided into four chapters. The first chapter is a preliminary one dealing with introductory matters, the purpose and stages of using the prospectus as a means of bringing to the attention of the public the shares and debentures which are being offered, as well as the usage and popularity of the method. The second chapter is devoted to the definitive elements of a prospectus as contained in the Act, with particular emphasis on the offer/invitation requirement as well as the advertisement element. While a prospectus is defined to include an advertisement, the latter is nowhere defined in the Act as a result of which a number of problems arise. For instructive guidance the statutory and judicial statements of an advertisement as a prospectus in the United Kingdom and Australia are discussed in considerable detail. The third chapter deals with the 'issue· concept. The link between the 'issue· requirement and 'public' is-given attention. It will be demonstrated that the Act itself in prohibiting the issue, distribution or publishing of a written statement in section 141 had, in fact, given indication of the probable meaning to be attached to the term. It will further be indicated the 'issue· required by the Act must be an authorised one. Finally, the 'issue' as used in the Act will be distinguished from its usage in other areas of our law. The fourth and final chapter of the thesis deals with the 'public' concept. It is intended to show that this is the thrust of the prospectus provisions. Hardships brought about by absence of a definition of the term will be pointed out. The paper further looks into problems created by allegations that the field of application of section 141 is as regards share hawking. It will be demonstrated that the allegations hold no truth. The South African cases dealing with the term 'public· are given a thorough treatment. Furthermore, the wide definition of 'offer to the public' in section 142 and its limitations in section 144 are studied in detail. Due to scarcity of judicial pronouncements on the concept 'public' in our law, the decisions in America, Australia and the United Kingdom, the various approaches and tests therein laid down form the central core of this work. In the light of the state of law in other jurisdictions and the inconclusive approach in our case law, a conclusion is reached that the law be amended by the definition of the term 'public' to be included in our section 142 and thus help. alleviate the obscurity prevalent at the moment.